Sexual history taking: Doctors' clinical decision-making in primary care in the North West province, South Africa - Deidré Pretorius; Ian D. Couper; Motlatso G. Mlambo (AOSIS, 2021)
Background: Clinical reasoning is an important aspect of making a diagnosis for providing patient care. Sexual dysfunction can be as a result of cardiovascular or neurological complications of patients with chronic illness, and if a patient does not raise a sexual challenge, then the doctor should know that there is a possibility that one exists and enquire. Aim: The aim of this research study was to assess doctors' clinical decision-making process with regards to the risk of sexual dysfunction and management of patients with chronic illness in primary care facilities of the North West province based on two hypothetical patient scenarios. Setting: This research study was carried out in 10 primary care facilities in Dr Kenneth Kaunda health district, North West province, a rural health district. Methods: This vignette study using two hypothetical patient scenarios formed part of a broader grounded theory study to determine whether sexual dysfunction as comorbidity formed part of the doctors' clinical reasoning and decision-making. After coding the answers, quantitative content analysis was performed. The questions and answers were then compared with standard answers of a reference group. Results: One of the doctors (5%) considered sexual dysfunction, but failed to follow through without considering further exploration, investigations or management. For the scenario of a female patient with diabetes, the reference group considered cervical health questions (p = 0.001) and compliance questions (p = 0.004) as standard enquiries, which the doctors from the North West province failed to consider. For the scenario of a male patient with hypertension and an ex-smoker, the reference group differed significantly by expecting screening for mental health and vision (both p = 0.001), as well as for HIV (p 0.001). The participating doctors did not meet the expectations of the reference group. Conclusion: Good clinical reasoning and decision-making are not only based on knowledge, intuition and experience but also based on an awareness of human well-being as complex and multidimensional, to include sexual well-being.